Pengaruh Penggunaan E-Commerce, Literasi Akuntansi, dan Inovasi Layanan terhadap Kinerja Keuangan Usaha Mikro di Kota Batu - Ningtyas, Amadea Ayu; Sodik, M.; Nurhayati, Indah Dewi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Micro-Enterprises, as a sub-sector of UMKM play a strategic role in the local economy, particulary in creating employment and boosting economic growth. This study aims to investigate the influence of e-commerce utilization, accounting literacy, and service innovation on the financial performance of micro-enterprises. This research employs a quantitative approach with a correlational method. Data was collected through questionnaires distributed to 100 micro-enterprises owners using a snowball sampling technique. The data instruments used were validity tests, reliability tests, and classical assumption tests, which included normality, multicollinearity, and heteroscedasticity tests. This study uses primary data, and the data analysis technique is multiple linier regression with the aid of the SPSS program.The analysis result indicate that e-commerce utilization, accounting literacy, and service innovation simultaneously influence the financial performance of micro-enterprises in Batu City. Partially, the results show that e-commerce utilization and accounting literacy have a significant impact on the financial performance of micro-enterprises, while service innovation does not show a significant influence.